Long-run money demand - Luca Benati; Robert E. Lucas; Juan Pablo Nicolini; Warren E. Weber (University of Bern, Department of Economics, 2020)
We explore the long-run demand for M1 based on a dataset comprising 38 countries and relatively long sample periods, extending in some cases to over a century. The evidence supports the existence of a stable long-run relationship between the ratio of M1 to GDP and a short-term interest rate for a large majority of the countries. The log-log specification provides a good characterization of the data, with the exception of periods featuring very low interest rates. An extension of the theory that imposes limits on the amount households can borrow results in a truncated log-log specification, which is in line with what we observe in the data. We estimate the interest rate elasticity to be between 0.3 and 0.6.
Keywords: 330; Long-run money demand; Cointegration